An Interface‐Bridged Organic–Inorganic Layer that Suppresses Dendrite Formation and Side Reactions for Ultra‐Long‐Life Aqueous Zinc Metal Anodes. Issue 38 (16th July 2020) - Cui, Yanhui; Zhao, Qinghe; Wu, Xiaojun; Chen, Xin; Yang, Jinlong; Wang, Yuetao; Qin, Runzhi; Ding, Shouxiang; Song, Yongli; Wu, Junwei; Yang, Kai; Wang, Zijian; et al.
Abstract: Aqueous zinc (Zn) batteries (AZBs) are widely considered as a promising candidate for next‐generation energy storage owing to their excellent safety features. However, the application of a Zn anode is hindered by severe dendrite formation and side reactions. Herein, an interfacial bridged organic–inorganic hybrid protection layer (Nafion‐Zn‐X) is developed by complexing inorganic Zn‐X zeolite nanoparticles with Nafion, which shifts ion transport from channel transport in Nafion to a hopping mechanism in the organic–inorganic interface. This unique organic–inorganic structure is found to effectively suppress dendrite growth and side reactions of the Zn anode. Consequently, the Zn@Nafion‐Zn‐X composite anode delivers high coulombic efficiency (ca. 97 %), deep Zn plating/stripping (10 mAh cm −2 ), and long cycle life (over 10 000 cycles). By tackling the intrinsic chemical/electrochemical issues, the proposed strategy provides a versatile remedy for the limited cycle life of the Zn anode. Abstract : Building bridges : An interfacial bridged organic–inorganic (Nafion‐Zn‐X) protection layer is developed by complexing inorganic Zn‐X zeolite nanoparticles with Nafion, which shift the ion transport from channel transport (Nafion) to hopping transport in the organic–inorganic interface. This structure suppresses dendrite formation and side reactions to guarantee the long cycle life of the Zn anode in aqueous batteries.